The Relation Between Stock Prices and Inflationary Expectations: The International Evidence - Solnik, Bruno (Journal of Finance, 1983)
This paper provides empirical evidence on the relation between stock returns and inflationary expectations for nine countries over the period 1971–80. The Fisherian assumption that real returns are independent of inflationary expectations is soundly rejected for each major stock market of the world. Using interest rates as a proxy for expected inflation, our data provide consistent support for the Geske and Roll model whose basic hypothesis is that stock price movements signal (negative) revisions in inflationary expectations. Finally, a weak real interest rate effect was found for some of these countries.